Comparative Analysis of Crawler Crane Productivity in Girder Erection: A Theoretical Study and Direct Observation - Massayu Sekar Bawana; Milinda Nur Indah Puspita; I Nyoman Dita Pahang Putra (CIVED, 2025)
Every construction project, in general, has a specific and systematic method implementation program, such as the utilization of heavy equipment in girder erection work. This focus is selected based on the high technical complexity of girder erection work, so the productivity of heavy equipment greatly affects the work's success. The aim is to analyze the suitability between theoretical calculation of crawler crane productivity and direct observations in girder erection work and identify the factors that cause the productivity difference. This study combines the theoretical calculations and direct observations to evaluate the productivity of crawler cranes in girder erection work. Based on theory, the method of calculating crane productivity is done by analyzing the operating cycle time and productivity of crawler cranes. With the direct observations method, actual data is taken in the field, which is then calculated as the result of its productivity. From the results of this study, it is found that the results of crawler crane productivity in direct observation in the field have a higher productivity value compared to the productivity value in theoretical calculations, namely 1.51 units/hour, while in theoretical calculations, the productivity value is 1.060 units/hour. The difference in value is caused by several factors in the field, such as weather conditions, operational obstacles, and the operator's efficiency.